Nuclear localisation of NOVH protein: a potential role for NOV in the regulation of gene expression. Issue 2 (1st April 1999) - Perbal, B
Abstract : AIMS: To identify the NOV protein detected by immunofluorescence in the nucleus of human cancer cell lines to establish whether targeting to the nucleus reflects dual paracrine and intracrine biological functions of NOV, as has been reported previously for several signalling peptides and proteins. METHODS: Nuclear and cytoplasmic fractions were prepared from 143 and HeLa cells in which nuclear NOV protein was detected. Western blotting analysis of NOV proteins in both types of fractions was performed using two NOV specific antibodies. Confocal microscopy was used to visualise the nuclear NOV protein in HeLa and 143 cells. A yeast two hybrid screening system was used to isolate cDNAs encoding proteins able to interact with the human NOV protein. RESULTS: A 31/32 kDa doublet of NOV protein was identified in the nuclear fraction of 143 and HeLa cells. Because the antibodies were directed against the C-terminus of NOV, the 31/32 kDa NOV isoform is probably truncated at the N-terminus and might correspond to the secreted 32 kDa NOV isoform detected in cell culture medium. Confocal microscopy indicated that in addition to the cytoplasmic NOV protein already identified, a nuclear NOV protein was present in both the nucleoplasm and nucleoli of Hela and 143 cells. Screening of cDNA libraries prepared from HeLa cells, Epstein-Barr virus transformed lymphocytes, and normal human brain showed that the NOV protein interacts with the rpb7 subunit of RNA polymerase in a yeast two hybrid system. CONCLUSIONS: The NOV protein detected in the nucleus of 143 and HeLa cells is probably an N-terminus truncated isoform of the secreted 48 kDa NOV protein. A growing body of evidence suggests that novH expression is closely associated with differentiation in normal human tissues and that the nov gene encodes a signalling protein that belongs to an emerging family of cell growth regulators. The nuclear localisation of a NOV isoform potentially provides an additional degree of signalling specificity. The interaction of the NOV protein and the rpb7 subunit of RNA polymerase II in the two hybrid system suggests that NOV might be involved in regulating gene expression at the transcriptional level. As has already been suggested for several other nuclearly located cytokines, the NOV protein does not contain a typical nuclear localisation signal. Therefore, it is possible that it combines with either a receptor or a chaperone during its translocation. Disruption of the balance between the secreted and nuclear NOV isoforms might affect the putative autocrine and paracrine functions of NOV and might be of considerable importance in the development of cancers in which the expression of novH has been shown to be impaired.